The Effect of Personalized Feedback on Small Enterprises' Finances in Uganda - Antonia Grohmann; Lukas Menkhoff; Helke Seitz (Economic Development and Cultural Change, 2020)
This randomized controlled trial examines the effect of a new finance training style during which participants are given personalized feedback on their financial business outcomes in addition to a rule-of-thumb training approach. We compare this with the effects of a rule-of-thumb training by itself and a control group. Targeting about 500 small entrepreneurs in Uganda, we find that the personalized feedback training significantly improves outcomes at the 6-month horizon. The index of primary outcomes increases by 0.258 SD units, and overall savings improve by 0.257 SD units. Survey results suggest that feedback partly works by increasing motivation, in line with feedback intervention theory.
Keywords: O12; D22; O16; L26; 330; Financial Training; Feedback; Small Business Growth; Economic Development